Kontruksi Sosial : Pengelolaan Wilayah Konservasi Pantai Cemara Banyuwangi Oleh KUB Sekar Arum Dalam Upaya Peningkatan Kesejahteraan Melalui Sektor Ekowisata - Ida Tri Widiyaningsih; Alina Ratna Anjali; Galuh Putri Rahayu (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study is to examine how the development of cypress conservation in the coastal area of ​​Cemara Pancer Beach, Banyuwangi Regency. Spruce conservation itself aims to rebuild forests that have been damaged by the tsunami in 1994, so that the coast will no longer become arid, and minimize the impact caused by tidal floods and coastal abrasion. With the conservation of fir in the coastal area, the coastal area becomes cooler and shady, so that people from outside the city and within the city are interested in visiting and enjoying the beauty of the cypress beach. Then, from this, economic and tourism activities can be built in the surrounding area. So that this can improve the welfare of the community through ongoing economic activities.